Profile of Junior High School Students’ Scientific Literacy - Muhammad Novaldy Nur Dwinanda Wahab; Wasis Wasis; Yuliani Yuliani (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This research is a preliminary study that aims to describe the scientific literacy skills of junior high school students based on tests using questions with indicators of scientific literacy skills, according to PISA. Method: This research was quantitative descriptive analysis research that used 20 questions with indicators of scientific literacy skills to measure the level of students' scientific literacy skills. Data were collected using a purposive sampling technique to obtain a sample of 102 students from 3 schools in Banjarmasin. Findings: Based on the research results obtained from 102 students, 11 had scientific literacy skills at level 5 or with good criteria. Then, 29 students are at the level of scientific literacy skill level 4 with enough criteria. Furthermore, 37 students are at the level of scientific literacy skills level 3 with deficient criteria. Moreover, 25 students are still at the level of scientific literacy skills level 2 with low criteria. Based on the results of this study, it is necessary to have follow-up efforts and more attention from related teachers to focus more on developing students' scientific literacy skills in the future. Novelty: The research novelty was to explain each level of scientific literacy ability that students reach. Hopefully, these things will be more helpful for further research, because the data that is presented is not just about the percentage of the quantity number. However, it is already explained in more detail.